“Contrariando a estatística”: a tematização dos homicídios pelos jovens negros no Brasil - Ramos, Paulo César (2014)
Homicides in Brazil have become a major social problem in recent decades. Young black males are the main victims. This paper presents a genealogy of the way black young people have brought the theme of murder and violence against blacks to the national agenda, from spaces of social participation, the black social movement and public youth policies. We conducted about 20 interviews with militants from black movements and other actors related to the topic. We also use data from fieldwork and participant observation, as well as reports, manifests, pamphlets and photographs, in order to understand when and how long these problems have been thematized. We tried to reflect on how the black movement thematicises violence / murder, its limits and potentials, contradictions and innovations in dialogue with social theory about recognition, identity and race relations. It has been possible to identify important moments of the trajectory of black movement, for example: violence as a reason for both performing public acts and for the emergence of organizations, such as the Unified Black Movement (MNU) until the 2000s; violence as the strongest theme of rap lyrics; and, in the last 15 years, violence / homicides against black youth as a central reason for the emergence of black youth as a new category of political action. In this work, gained prominence the Youth Alive Plan (2012-2013), the Working Group Black Youth and Public Policies of the National Youth Council (2008-2010), and The First National Conference of Black Youth (2005-2008) . Among the various ways of categorizing this issue, the term "genocide" draws attention - the was first used by Abdias do Nascimento to denounce racism and it is now widely used by social movements. Among the various forms of organization of young blacks, the claim for leadership of a brand new generation of militants is also emerging, with a set of experiences that allow them to create semantic bridges to act on the institutional sphere and demand public policies against violence.